Memahami Strategi Komunikasi Pemasaran Kartu Brizzi PT Bank BRI, Tbk. Kanwil Semarang - Febriana, Widia (Universitas Semarang, 2015)
With increasing public awareness of the technology, there are a trend the demand for banking products based on technology, in particular transactions through cards. But the public's knowledge about the e-money making product marketing e-money is still lacking. To overcome this, we need a marketing communication strategy of e-money is appropriate and effective. The cornerstone of the theory used in this study the theories of Kotler Kotler, said that elements of the promotion mix (promotion mix) consists of five main device, namely: Advertising, Sales Promotions, Public Relations and publicity, Personal Selling and Direct Marketing. This research aims to determine the effectiveness of of the activities of marketing communications strategy that has been done. To analyze the marketing communication strategies, conducted research at PT. Bank Rakyat Indonesia (Persero) Regional Office Semarang. Data collected from various sources consisting of external factors and internal, ie interviews, observation and documentation. Furthermore, these factors were analyzed to get the strategy formulation. Resource persons / informants consists of the CBK offices and the Customer card user Semarang BRIZZI. All of the strategies undertaken in marketing BRIZZI, the most effective way is to give the gift of groceries to customers BRIZZI users when shopping at the supermarkets in Semarang.